Incidence of unintended pregnancy and associated factors among adolescent girls and young women at risk of HIV infection in Kampala, Uganda - Namukisa, Mary; Kamacooko, Onesmus; Lunkuse, Jane Frances; Ruzagira, Eugene; Price, Matt A.; Mayanja, Yunia (Frontiers in Reproductive Health, 2023)
Background In sub-Saharan Africa, one in every five young women becomes pregnant, and 50% of these are unintended. Pregnancies in adolescent girls and young women (AGYW) are associated with poorer maternal and neonatal outcomes and a high abortion rate, yet data are still limited on incident pregnancies among AGYW in vulnerable situations. We studied the incidence and factors associated with unintended pregnancy among AGYW who were frequently engaged in transactional sex in Kampala, Uganda. Methods We analyzed data from a study that investigated the uptake of oral pre-exposure prophylaxis among AGYW from January 2019 to December 2020. Volunteers attended 3-monthly study visits for 12 months each. Contraceptive services were provided to interested volunteers free of charge. Interviewers collected data on sociodemographics, sexual behavior, reproductive health outcomes, and substance use. Pregnancy was determined by testing for beta-human chorionic gonadotropin hormone in urine. The pregnancy incidence rate was estimated using the Kaplan–Meier technique, and logistic regression was used to determine the correlates of pregnancy. Results We included 285 volunteers with a mean age of 19.9 [standard deviation (SD), ± 2.24] years; 54.7% had attained secondary school education or higher, 57.2% were single (never married), 92.6% reported engaging in transactional sex, 21.0% reported sex work as their main job, 51.9% consumed alcohol in the month prior to the interview, of whom 12.8% consumed alcohol daily, and 25.3% had Chlamydia trachomatis/Neisseria gonorrhoeae. The mean age at first sexual intercourse was 15.7 (SD, ±2.1) years. We recorded 44 pregnancies over 187.2 person-years of follow-up, an incidence of 23.5 per 100 person-years [95% confidence interval (CI), 17.5–31.6]. Incident pregnancies were more likely among volunteers who had ≥10 sexual partners in the past 3 months [adjusted risk ratio (aRR) 1.97; 95% CI, 1.05–3.70] and those who reported not using contraception (aRR 5.89; 95% CI, 2.74–12.66). Incident pregnancies were less likely among those who reported alcohol consumption in the past month (aRR 0.52; 95% CI, 0.30–0.90). Conclusion The incidence of unintended pregnancy was high despite the availability of free contraceptive services. We recommend sociobehavioral studies to explore this further. Sexual and reproductive health campaigns should strengthen demand creation and motivation to use contraception among young women with multiple sexual partners.